Analisis Nilai Pendidikan Karakter Dalam Cerita Rakyat Mentawai Di Desa Mara Kabupaten Kepulauan Mentawai - Aneka Nonaria; Eva Fitrianti; Dwi Mutia Chan (Kilau Publishing, 2025)
In the past, parents used stories as a medium to give advice and provide education to their children. However, many young people are no longer familiar with the character education values contained in the folktales of Mara Village, and even among the people of Mara Village, only some are aware of these values. This may be due to rapid changes and advances in technology. This study aims to describe and analyze the character education values in Mentawai folktales in Mara Village, Mentawai Islands Regency. This research used a descriptive method. The results show that the researcher found 10 Mentawai folktales classified as fairy tales. Overall, the character education values found were honesty with 11 data, curiosity with 18 data, independence with 2 data, hard work with 10 data, discipline with 2 data, responsibility with 3 data, environmental care with 2 data, social care with 5 data, tolerance with 2 data, peace-loving with 1 datum, appreciation of achievement with 1 datum, and religiosity with 4 data. In conclusion, the overall results of the study found 61 data related to character education values. The dominant character education value was curiosity.